Avatar, the last airbender. Imbalance. Part one - Hicks, Faith Erin (Dark Horse Books, 2018)
Team Avatar returns to Toph's father's factor to find that the town has substantially grown. And they find themselves in the heart of a conflict that threatens to tear the community apart.